Characteristics of Lactic Acid bacteria isolated from traditional fermented fish (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Novia R, Ardiningsih P, Adhityawarman, Sarwiyati. 2022. Characteristics of Lactic Acid bacteria isolated from traditional fermented fish. Biodiversitas 23: 5662-5669. Lactic acid bacteria (LAB) are commonly involved in most food fermentation and contribute to the process’s quality and safety. The study investigates the characteristics of LAB isolated from buduk, pekasam, and pekasam ale-ale. Twelve colonies each sample were isolated and identified based on morphology and biochemical test. The pekasam ale-ale isolates were identified as Pediococcus sp. strain A1 and Pediococcus sp. strain A3; Enterococcus sp. strain A2 and Enterococcus sp. strain A4. The LAB in buduk were identified as Streptococcus sp. strain B1, Pediococcus sp. strain B2 and Pediococcus sp. strain B4, Enterococcus sp. strain B3. The pekasam isolates were identified as Pediococcus sp. strain P1, Streptococcus sp. strain P2 and Streptococcus sp. strain P4, Lactobacillus sp. strain P3. The LAB showed antimicrobial activities while Lactobacillus sp. strain P3 and Streptococcus sp. strain P4 could grow at pH 1. Two LAB including Enterococcus sp. strain A2 and Pediococcus sp. strain P1 showed amylase activity while Pediococcus sp. strain A3, Streptococcus sp. strain B1, Pediococcus sp. strain B2, Enterococcus sp. strain B3 showed protease activity. All LAB produced organic acids with varying concentrations at different incubation times. Furthermore, those isolated from various fish fermentations showed different genera and characteristics. Lactobacillus sp. strain P3 was the best to initiate food fermentation and a probiotic candidate based on their characteristics.
Keywords: Buduk, fish fermentation, Lactic acid bacteria, pekasam, pekasam ale-ale